Taxonomic revision of Marma Simon, 1902 (Araneae: Salticidae: Euophryini) - Salgado, Alexandre; Ruiz, Gustavo R.s. (Zootaxa, 2020)
The Neotropical genus Marma Simon, 1902 is revised. With exception of the holotype of M. femella (Caporiacco, 1955), which was redescribed in previous work, all the other species of the genus were revised based on their types. The type species, M. baeri Simon, 1902, and M. nigritarsis (Simon, 1900) are redescribed based on newly collected specimens. The third and last species presently listed in the World Spider Catalog, M. femella, is confirmed as valid. Two species presently considered synonyms of M. nigritarsis are revalidated: M. rosea (Mello-Leitão, 1941) and M. argentina (Mello-Leitão, 1941). Two species are synonymized: Thysema dorae Mello-Leitão, 1944, syn. nov. with Ocnotelus argentinus Mello-Leitão, 1941 and Paralophostica centralis Soares & Camargo, 1948, syn. nov. with Agelista rosea Mello-Leitão, 1941. Pseudoamphidraus variegatus Caporiacco, 1947 and M. trifidocarinata Caporiacco, 1947 are confirmed as synonyms of M. nigritarsis. Six new species from northern/northeastern Brazil are described: M. abaira sp. nov. (♀), M. linae sp. nov. (♂♀), M. pipa sp. nov. (♂♀), M. sinuosa sp. nov. (♂♀), M. spelunca sp. nov. (♂♀) and M. wesolowskae sp. nov. (♂♀). Also, the male of M. argentina is described for the first time. We give new diagnostic illustrations and updated distribution records for all the species of the genus.